E-psybermatrix : psychological profile web based expert system software - Syed Yahya, Syed Mohd. Asri (2007)
The past decade has witnessed a rapid expansion of the Internet. This revolutionary communication network has significantly changed the way people conduct business, communicate, and live. This is why the report tries to focus on how the computer and internet technology can be used to develop e-Psybermatrix: Psychological Profile Web Based Expert System software. The report includes topics such as background problem and solution of psychology profiling in Malaysia, literature review on current practice, methodology that needed in the development and initial finding of technical design. Special attention is paid to business plan that defines commercial value of this State-of-the-Art Technology. The target web application in this development is Personality Profile, Career Interest Profile, Stress Profile, Entrepreneur/Technopreneur Profile, and Psychological Profile Knowledge-base Management System. The report also covers issues specific to areas of practice such as psychological, industrial/organizational, educational, and personality. The most salient conclusion from this report is that the powerful of computer science as an enabler, particularly those regarding the effective usage of psychological profile. Still, new methods made possible by emerging technologies such as Java 2 Enterprise Edition (J2EE), Unified Modelling Language (UML), Web Based Expert System Methodology and Open Source will push the boundaries of existing psychometric theory and it is up to practitioners to test and expand the limits of psychometrics to keep pace with these innovations. This project encourages practitioners to think creatively about how their research and practice can be improved by Internet based profiling. Although there are many issues that await resolution, practitioners should look forward to this new medium with excitement and enthusiasm towards maturity, quality, and productivity of human capital in the future.